Comparison of neuropsychological functioning in pediatric posterior fossa tumor survivors: Medulloblastoma, low‐grade astrocytoma, and healthy controls. Issue 2 (29th November 2021) - Levitch, Cara F.; Holland, Alice Ann; Bledsoe, Jesse; Kim, Soo Young; Barnett, Marie; Ramjan, Sameera; Sands, Stephen A.
Abstract: Background: Neuropsychological comparison of medulloblastoma (MB) and cerebellar low‐grade astrocytoma (LGA) survivors to controls can clarify treatment‐related neurocognitive late effects. While both brain tumor groups undergo surgery to the posterior fossa, children with MB additionally receive craniospinal irradiation with boost and chemotherapy. This study provides an updated comparison of neuropsychological functioning in these two groups and examines effects of demographic risk factors upon outcomes. Procedure: Forty‐two children (16 MB, nine LGA, and 17 controls) completed measures of intellectual functioning, verbal learning/memory, visual–motor integration, and fine‐motor functioning. The effects of age at diagnosis, time since diagnosis, gender, fatigue, and social status on neuropsychological functioning were examined. Results: MB survivors demonstrated the worst neurocognitive late effects, but they were less severe and extensive than in prior studies. LGA survivors' mean scores were below normative expectations in working memory, processing speed, and fine‐motor functioning. In this overall sample, processing speed difficulties were independent of fine‐motor functioning and fatigue. Higher parental education was associated with better intellectual functioning, working memory, delayed recall, and visual–motor integration. Neuropsychological function was not associated with gender, age at diagnosis, or time since diagnosis. Conclusion: The results support that contemporary treatment approaches with craniospinal irradiation plus boost and chemotherapy confer the greatest risk for late effects, while surgical resection is associated with subtle but important neurocognitive difficulties. Ultimately, this study furthers our understanding of factors impacting neuropsychological function in pediatric MB and LGA survivors and contributes to empirical support for close monitoring and targeted interventions into survivorship.